Angiographische okkulte Gefässmissbildungen im Gebiet des Pons. Zwei Fallberichte - Marák, R; Muchová, B (Der Nervenarzt, 1993)
On the basis of two case reports of occult vascular malformation of the pons that had been followed since the first clinical manifestation, clinical picture, diagnosis using modern imaging methods (especially magnetic resonance imaging--MRI) and therapy of this disease are discussed. In addition to a precise localization diagnosis based on typical scans of varying signal intensity, particularly after bleeding, MRI also allows a preoperative qualitative identification of the lesion and provides important information about the dynamics of the process. Further experience with this uncommon clinical category will improve the early diagnosis and selection of an adequate therapy because the technique of stereotactic radiotherapy (gamma-knife) appears to be most suitable.
Keywords: Magnetic Resonance Imaging; nádory mozku; Hypophysectomy; magnetická rezonanční tomografie; intrakraniální arteriovenózní malformace; Humans; diferenciální diagnóza; Empty Sella Syndrome; Brain Neoplasms; Female; hypofyzektomie; dospělí; Diagnosis, Differential; lidé; pons; Cerebral Angiography; Neurologic Examination; neurologické vyšetření; radiochirurgie; Adult; Postoperative Complications; Radiosurgery; mozková angiografie; pooperační komplikace; ženské pohlaví; Pons; syndrom prázdného sedla; hemangiom; Subarachnoid Hemorrhage; Intracranial Arteriovenous Malformations; Hemangioma; subarachnoidální krvácení